Praktične rešitve za uporabo podportala e-Izvršba - Mejač, Barbara (Podjetje in delo, 2013)
The article deals with issues of the Slovenian information system e-Izvršba (e-Enforcement) launched in March 2012. First, it describes the information system, conditions under which a person can become a user of the web portal e-Judiciary and under which he/she can use e-actions on the sub-portal (e-Enforcement). The author provides answers to some frequently asked questions by users and explains why the use of the sub-portal e-Izvršba is more suitable than classical contact with the court. The author concludes by indicating the further development of electronic operation in enforcement and securing of civil claims proceedings.
Keywords: elektronsko poslovanje; informacijski sistemi; izvršba; izvršilni postopek; sodne odločbe; sodni postopek